GENDER BIAS IN WEBTOON THE SECRET OF ANGEL BY YAONGYI: GENDER EQUALITY IN THE WORLD OF MAKEUP - Itgo Hatchi; Mutia Nasution (Jurnal Ilmu Pendidikan Ahlussunnah, 2023)
This research discusses the study of gender bias in Webtoon The Secret of Angel by Yaongyi. The data in this study are excerpts of dialogue that lead to gender bias, especially those in contact with male characters contained in the stories expressed by the author in Webtoon digital comics. The data source for this research is Webtoon The Secret of Angel by Yaongyi which was published in 2018 which consists of 223 episodes. The instruments in this study were the researchers themselves and documents in the form of conversations that described the categories of gender bias experienced by male characters. The results of this research show that gender bias or gender injustice is not only experienced by woman but also by man, it is concluded that the male character in Webtoon The Secret of Angel by Yaongyi named Seungho experiences gender bias or gender injustice from the family and community where he lives.